Cancer : principles & practice of oncology. - DeVita, Vincent T., Jr., 1935-; Lawrence, Theodore S.; Rosenberg, Steven A. (Wolters Kluwer, 2015)
Understand and apply the scientific advances that are revolutionizing cancer research and practice! Derived from DeVita, Hellman, and Rosenberg's Cancer: Principles and Practice of Oncology - widely hailed as the definitive clinical reference in oncology - the second editon of this popular Primer focuses on the molecular biology information that is of critical importance to research scientists and clinical oncologists alike. Get up-to-date, dependable coverage of every important frontier in the molecular biology of cancer with contributions from a noteworthy roster of leading scientists and clinicians, featuring an updated version of the classic "Hallmarks of Cancer" by Hanahan and Weinberg. See how molecular biology advances are impacting clinical practice with separate chapters on each of the 19 most common cancer types. Navigate the challenges and ethical dilemmas of cancer genetics with a thorough section chapters on genetic counseling and genetic testing. Now with the print edition, enjoy the bundled interactive eBook edition, offering tablet, smartphone, or online access to: Complete content with enhanced navigation, A powerful search that pulls results from content in the book, your notes, and even the web, Cross-linked pages, references, and more for easy navigation, A Highlighting tool for easier reference of key content throughout the text, Ability to take and share notes with friends and colleagues, Quick reference tabbing to save your favorite content for future use, See the inside front cover to find out how to access your eBook! Book jacket
Abridgement of: Devita, Hellman, and Rosenberg's cancer. 10th edition. [2015]
Keywords: Cancer -- Genetic aspects; Neoplasms -- genetics; Neoplasms -- physiopathology; Cancer -- Molecular aspects